Patients with acute myelogenous leukemia (AML) from a socially disadvantaged environment show poorer therapeutic outcome - Kaifie, Andrea; Lunau, Thorsten; Dragano, Nico; Jost, Edgar; Brümmendorf, Tim H.; Wilop, Stefan; Crysandt, Martina (Journal of Public Health, 2017)
Aim: Socioeconomic position (SEP) has a significant influence on the clinical course of several diseases. For acute myelogenous leukemia (AML), only limited data on the association between SEP and Overall Survival (OS) are available. Subject and methods: In this retrospective study, we divided the city of Aachen (approx. 250,000 inhabitants) into areas with middle/high as opposed to low socioeconomic background using the official social development plan. Using these data, the outcome of 135 AML-patients who were treated at the RWTH Aachen University Hospital, was analyzed. Results: No significant differences in the distribution of established prognostic factors could be detected between the two SEP areas. For patients who received treatment with curative intention, we found a significantly impaired OS for those living in low compared to middle/high SEP areas (15.9 vs 28.8 months, p = 0.02). Furthermore, achievement of complete remission was significantly lower among those from low versus middle/high SEP areas (39.1 % vs. 73.0 %, p = 0.01), which is of particular interest given the fact that this study was performed in a health care system with obligatory health insurance. Conclusion: These data provide the basis for a detailed investigation on underlying mechanisms by which SEP affects AML survival and prognosis. Strategies to prevent this unsatisfactory situation need to be addressed.
CRIS-Team Scopus Importer:2023-09-25
Keywords: Acute leukemia; Determinants of health; Epidemiology; Health outcome; Public health